Treatment Advances in EBV Related Lymphoproliferative Diseases - Lv, Kebing; Yin, Ting; Yu, Min; Chen, Zhiwei; Zhou, Yulan; Li, Fei (Frontiers in Oncology, 2022)
Epstein Barr virus (EBV) can affect 90% of the human population. It can invade B lymphocytes, T lymphocytes and natural killer cells of the host and remain in the host for life. The long latency and reactivation of EBV can cause malignant transformation, leading to various lymphoproliferative diseases (LPDs), including EBV-related B-cell lymphoproliferative diseases (EBV-B-LPDs) (for example, Burkitt lymphoma (BL), classic Hodgkin’s lymphoma (cHL), and posttransplantation and HIV-related lymphoproliferative diseases) and EBV-related T-cell lymphoproliferative diseases (EBV-T/NK-LPDs) (for example, extranodal nasal type natural killer/T-cell lymphoma (ENKTCL), aggressive NK cell leukaemia (ANKL), and peripheral T-cell lymphoma, not otherwise specified (PTCL-NOS)). EBV-LPDs are heterogeneous with different clinical features and prognoses. The treatment of EBV-LPDs is usually similar to that of EBV-negative lymphoma with the same histology and can include chemotherapy, radiotherapy, and hematopoietic stem cell transplant (HSCT). However, problems such as serious toxicity and drug resistance worsen the survival prognosis of patients. EBV expresses a variety of viral and lytic proteins that regulate cell cycle and death processes and promote the survival of tumour cells. Based on these characteristics, a series of treatment strategies for EBV in related malignant tumours have been developed, such as monoclonal antibodies, immune checkpoint inhibitors, cytotoxic T lymphocytes (CTLs) and epigenetic therapy. These new individualized therapies can produce highly specific killing effects on tumour cells, and nontumour cells can be protected from toxicity. This paper will focus on the latest progress in the treatment of EBV-LPDs based on pathological mechanisms.